Leucosiid crabs from Papua New Guinea, with descriptions of eight new species (Crustacea: Decapoda: Brachyura) - Galil, Bella S.; Ng, Peter K. L. (Zootaxa, 2015)
Twenty-five species of leucosiid crabs are reported from Madang Province, Papua New Guinea. Of these, seven are new to science: two each are included in Alox Tan & Ng, 1995 and Tanaoa Galil, 2003, and one each in Ryphila Galil, 2009, Seulocia Galil, 2005, and Urnalana Galil, 2005. Fifteen additional species are new records for Papua New Guinea: Alox rugosum (Stimpson, 1858), Ancylodactyla nana (Zarenkov, 1990), Arcania heptacantha De Man, 1907, Heterolithadia fallax (Henderson, 1893), Hiplyra longimana (A. Milne Edwards, 1874), Myra curtimana Galil, 2001, M. digitata Galil 2004, Nursilia dentata Bell, 1855, Oreotlos etor Tan & Richer de Forges, 1993, Parilia major Sakai, 1961, Raylilia coniculifera Galil, 2001, R. uenoi (Takeda, 1995), Toru pilus (Tan, 1996), Urashima pustuloides (Sakai, 1961) and Leucosia rubripalma Galil, 2003. The new species are described and illustrated, and their affinities with allied taxa discussed. Colour photographs are provided for 20 species.